Antimutagenic effects of eighteen Philippine plants - Lim-Sylianco, C.Y; Concha, J.A; Jocano, A.P; Lim, C.M (1986)
Expressions from Cassia alata L., Anona squamosa L., Lagerstroemia speciosa (L.) Pers., Allium sativum L., Psidium guajava L., Capsicum annuum L., Allamanda cathartica L., Symphytum officinale L., Leucaena leucocephala Lamb.; Plumeria acutifolia Poir., Garcinia mangostana L., Phaseolus aureus Roxb., Quisqualis indica L., Blumea balsamifera (L) D.C., Allium cepa L., Spondias purpurea L., Carmona astusa (Voh 1) Masam, and Mentha cordifolia L., reduced the induction of micronucleated polychromatic erythrocytes by mitomysin C., dimethylnitrosamine and tetracycline showing that these plants have antimutagenic effects. Heating did not affect the antimutagenic property of the plants.